Detection of S-Nitrosothiols - Diers, Anne R. (Biochim Biophys Acta, 2013)
BACKGROUND: S-Nitrosothiols have been recognized as biologically-relevant products of nitric oxide that are involved in many of the diverse activities of this free radical. SCOPE OF REVIEW: This review serves to discuss current methods for the detection and analysis of protein S-nitrosothiols. The major methods of S-nitrosothiol detection include chemiluminescence-based methods and switch-based methods, each of which comes in various flavors with advantages and caveats. MAJOR CONCLUSIONS: The detection of S-nitrosothiols is challenging and prone to many artifacts. Accurate measurements require an understanding of the underlying chemistry of the methods involved and the use of appropriate controls. GENERAL SIGNIFICANCE: Nothing is more important to a field of research than robust methodology that is generally trusted. The field of S-Nitrosation has developed such methods but, as S-nitrosothiols are easy to introduce as artifacts, it is vital that current users learn from the lessons of the past.